Do picadeiro ao céu : o riso no teatro de Ariano Suassuna - Caldas Neto, Paulo de Macedo (2008)
The analysis of this work seeks to investigate the meaning of the laughter in the paraibano writer Ariano Suassuna s armorial theater. The study departs, firstly, from an argumentation which centers its content in the theory of the many theoreticians of the question: Henri Bergson, Vladimir Propp, Jolles, Freud, Bakhtin. The essence of the laughter in Suassuna and its esthetic relations are commented, because those elements are responsible for the strength of the literary text. On the condition of scholar about Esthetic and Art History, Suassuna always puts the methods of the estheticism in favor of the loud laughter bearing in mind that it is a source of improvisation, i.e., it may have many senses depending on what it is pretended to transmit to the reader/viewer. The laughter is a mask which is changed to each new situation, representing that way own human condition. Because the theater is an art subjected to recreation, the laughter also is. And because it is a great party where other arts (the dance, the music, mamulengo e the bumba-meu-boi) are present, united to compose a confluent and hybrid language, the meaning of hilarity during the popular celebrations is studied mainly those that happened in Medieval Europe. Thus, in the second part, the basis of the research is the Russian Mikhail Bakhtin s theory that helps to link Suassuna s laughter to the popular party, showing the language used in them and the jokes that give life to the joy of the folk. Soon after, the importance of Suassuna s laughter to the Brazilian Culture, is examined making a reflection about its function at the sociocultural context of the country